Pharmacological considerations in the elderly. Issue 1 (February 2018) - Akhtar, Shamsuddin
Abstract : Purpose of review: This review discusses the pharmacology of contemporary anesthetic medications in geriatric patients, neurophysiological changes with aging, current recommendations for dosing anesthetic drugs. It also addresses current practice patterns and ongoing studies, which are likely to affect future anesthetic drug management in the elderly. Recent findings: Potency of anesthetic drugs is increased in the elderly. In addition to changes at the receptor level, neurophysiological changes in functional connectivity with aging contributes to increased sensitivity of anesthetic drugs. However, the extent of reduction is underappreciated by the practitioners and dose adjustment is not uniformly applied in practice. Large database studies demonstrate association of short-term intraoperative hypotension and CNS depression, to poor perioperative outcomes. These perturbations are probably of greater consequence in frail, elderly patients with reduced reserves. Summary: Anesthetic dosing should be more closely age-adjusted to prevent anesthetic-induced hypotension and increased depth of anesthesia in the elderly. Pharmacologic studies are required in the elderly population (>80 years).